Pengaruh AVA (Audio Visual Aids) terhadap Kemampuan Latihan Paska Operasi Laparotomi - Agus Susanto; Erni Setiyorini (Journal of Ners and Midwifery, 2014)
Introduction: Health education is the important experience of surgery to client that can used audio visual aids.  The purpose of this study was to identify the effect of audio visual aids to the capability exercise post laparotomy. Method: Research design was quasy experiment non equivalent control group design. Research sample was 20 patients whose laparotomy at Mardi Waluyo Hospital Blitar at May 25th until June 16th, 2012, its choosed with accidental sampling. The data collected by observation using checklist. Analysis using independent sample T-Test, with ≤0.05 significant level. Result: The results showed that audio visual aids at health education influence capability exercise post laparatomy, with p value 0.000. Discussion: Using tool and method appropriate at health education pre operatif effective to improve output learning.   Keywords: audio visual aids, exercise, laparotomy